Enabling Futures: Equity and Innovation in Higher Education - James, Trixie; Miller, Stephen (Journal of University Teaching and Learning Practice, 2025)
Widening participation (WP) in higher education (HE) remains a global “wicked problem,” marked by persistent structural inequities despite decades of reform. This editorial introduces the Fostering Inclusion in Higher Education: Global Approaches to Widening Participation special issue, situating Australia’s experience within an international dialogue on equity and innovation. In Australia, WP has evolved over more than 80 years, driven by intersecting imperatives of social justice and national economic development. Enabling programs, fee-free, preparatory pathways, represent a cornerstone of this agenda, providing accessible routes into university for students from low socioeconomic, Indigenous, regional, and other equity backgrounds. Rather than being simply remedial, these programs function as sites of social innovation, fostering confidence, capability, and transformative agency through pedagogies grounded in care and critical engagement. Their success in improving access, retention, and graduate outcomes underscores their role in meeting ambitious national targets, including those outlined in the Australian Universities Accord, and advancing global commitments such as the United Nations Sustainable Development Goals. International comparisons reveal shared challenges, including deficit discourses and entrenched barriers, alongside common strategies that prioritise inclusive pedagogy and holistic support. By amplifying diverse perspectives and evidence-based practices, this special edition contributes to consolidating the knowledge base of Enabling education and its equivalents worldwide. Ultimately, WP is not merely about access but empowerment, transforming HE into an engine of equity and sustainability.